Pendekatan Living Values Education dalam Menanamkan Nilai Karakter Anak di RA Tiara Chandra Yogyakarta (PIAUD IAIN Kudus, 2020)
LIVING VALUES EDUCATION APPROACH IN DEVELOPING CHILDREN’S CHARACTER AT RA TIARA CHANDRA YOGYAKARTA. This study aims to find out how the Living Values Education (LVE) approach in instilling the character values of children in RA Tiara Chandra Yogyakarta. The research used qualitative method with a case study approach. Data collection techniques carried out through participatory observation, in-depth interviews, and documentation, while data analysis technique are through data reduction, data display, and verification. The results showed that RA Tiara Chandra has used the LVE approach for the past three years, starting with the training given to teachers and staff as role models for children, then involving parents and the community around the school area. Training of adults was the first step to guide children in developing character values. This step was quite effective and had a positive impact on the development of children's character values in RA Tiara Chandra Yogyakarta.